Navigational choice between reversal and curve during acidic pH avoidance behavior in Caenorhabditis elegans. Issue 1 (December 2015) - Wakabayashi, Tokumitsu; Sakata, Kazumi; Togashi, Takuya; Itoi, Hiroaki; Shinohe, Sayaka; Watanabe, Miwa; Shingai, Ryuzo
Abstract Background Under experimental conditions, virtually all behaviors ofCaenorhabditis elegans are achieved by combinations of simple locomotion, including forward, reversal movement, turning by deep body bending, and gradual shallow turning. To study how worms regulate these locomotion in response to sensory information, acidic pH avoidance behavior was analyzed by using worm tracking system. Results In the acidic pH avoidance, we characterized two types of behavioral maneuvers that have similar behavioral sequences in chemotaxis and thermotaxis. A stereotypic reversal-turn-forward sequence of reversal avoidance caused an abrupt random reorientation, and a shallow gradual turn in curve avoidance caused non-random reorientation in a less acidic direction to avoid the acidic pH. Our results suggest that these two maneuvers were each triggered by a distinct threshold pH. A simulation study using the two-distinct-threshold model reproduced the avoidance behavior of the real worm, supporting the presence of the threshold. Threshold pH for both reversal and curve avoidance was altered in mutants with reduced or enhanced glutamatergic signaling from acid-sensing neurons. Conclusions C. elegans employ two behavioral maneuvers, reversal (klinokinesis) and curve (klinotaxis) to avoid acidic pH. Unlike the chemotaxis inC. elegans, reversal and curve avoidances were triggered by absolute pH rather than temporal derivative of stimulus concentration in this behavior. The pH threshold is different between reversal and curve avoidance. Mutant studies suggested that the difference results from a differential amount of glutamate released from ASH and ASK chemosensory neurons.